2019
DOI: 10.3390/app9081705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercritical Quenching Temperature of Cu-Containing Low Alloy Steel of Long Part Forging for Offshore Applications

Abstract: In our previous study, intercritical quenching from the dual-phase region of ferrite and austenite regions, which is called lamellarizing (L) treatment, brought a clear improvement of balance between the strength and toughness of Cu-containing low alloy steel based on American Society for Testing and Materials (ASTM) A707 5L grade. Moreover, the results imply that the reverse transformation behavior during L treatment is very important in order to optimize the L treatment temperature. Hence, the purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Sample 1.6511Si2V has the highest volume fraction of retained austenite among the samples; despite the larger grain size due to the possibility of simultaneous blinding and the TRIP phenomenon resulting from its retained austenite, it was able to absorb great energy before failure. Rare earth elements, besides decreasing the grain size, which leads to increased fracture toughness [45][46][47][48][49][50][51][52], also increase the grain boundary strength [36]. It seems that there is an increase in energy required for the fracture of the 1.6511Si2M sample compared to the standard sample, and the 1.6511Si2 sample has a higher grain boundary volume and higher grain boundary strength compared to other samples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Sample 1.6511Si2V has the highest volume fraction of retained austenite among the samples; despite the larger grain size due to the possibility of simultaneous blinding and the TRIP phenomenon resulting from its retained austenite, it was able to absorb great energy before failure. Rare earth elements, besides decreasing the grain size, which leads to increased fracture toughness [45][46][47][48][49][50][51][52], also increase the grain boundary strength [36]. It seems that there is an increase in energy required for the fracture of the 1.6511Si2M sample compared to the standard sample, and the 1.6511Si2 sample has a higher grain boundary volume and higher grain boundary strength compared to other samples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Haiko et al [3] investigate the influence of tempering temperature on both the microstructure and monotonic stress-strain response in a new ultra-high-strength steel with low carbon content. Honma et al [4] analysed the effect of intercritical quenching temperature on the strength and toughness in a low-alloy steel developed for offshore applications. Gu et al [5] developed a numerical approach to evaluate the effect of different inclusions on the residual stress profiles during the cooling process for martensitic steels.…”
Section: Contributionsmentioning
confidence: 99%
“…Li [29] reported that through introducing an intercritical quenching process between conventional quenching and tempering to 25Mn2Si2Cr bainitic steel, the tensile strength, yield strength and impact energy value exhibited an enhancement by 5.4%, 3.2% and 20.7%, respectively. The optimum combination of strength and toughness results from the refinement of complicated microstructures and grains, higher fraction of high angle grain boundaries caused by the formation of ferrite, abundant homogeneous dislocation cell substructure and stable thin film retained austenite [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%